2017
DOI: 10.1021/acsbiomaterials.7b00679
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial Property Effects on Platelets and Macrophages: An in Vitro Study

Abstract: The purpose of this study was to evaluate the effects of surface properties of bone implants coated with hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) on platelets and macrophages upon implant installation and compare them to grit-blasted Ti and Thermanox used as a control. Surface properties were characterized using scanning electron microscopy, profilometry, crystallography, Fourier transform infrared spectroscopy, and coating stability. For platelets, platelet adherence and morphology were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…Gu et al [ 64 , 65 ] explored whether introducing a certain amount of β-TCP into calcium phosphate cement could promote M polarization to the anti-inflammatory phenotype (M2) in long-term culture. In contrast, Tai et al [ 66 ], Chen et al [ 67 ], and Fernandes et al [ 68 ] found that β-TCP, its extract, and its use as a coating on a Ti surface were strong enough to induce M1 polarization of M s. Chen et al [ 69 ] also identified that β-TCP maintained a high proportion of iNOS + M1-polarized M s both in vitro and in vivo. In our study, TCP was wrapped in PLLA to form a porous structure.…”
Section: Discussionmentioning
confidence: 99%
“…Gu et al [ 64 , 65 ] explored whether introducing a certain amount of β-TCP into calcium phosphate cement could promote M polarization to the anti-inflammatory phenotype (M2) in long-term culture. In contrast, Tai et al [ 66 ], Chen et al [ 67 ], and Fernandes et al [ 68 ] found that β-TCP, its extract, and its use as a coating on a Ti surface were strong enough to induce M1 polarization of M s. Chen et al [ 69 ] also identified that β-TCP maintained a high proportion of iNOS + M1-polarized M s both in vitro and in vivo. In our study, TCP was wrapped in PLLA to form a porous structure.…”
Section: Discussionmentioning
confidence: 99%
“…More comprehensive studies are required to pinpoint the surface properties most relevant for specific biological responses, as well as to eliminate bias when comparing results from different experimental concepts (cellular models, interspecies differences, and readout parameters). For this reason, we employed three in vitro models of the human immune system, ranging in degree of biological complexity from simple to complex: We chose a model based on THP-1-derived macrophages because this is widely regarded as a valid model to investigate biomaterials, particularly due to its demonstrated ability to relate to the host response in vivo [18][19][20][21]. Due to its reduced complex biology, this model also affords several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The surface-adsorbed proteins participate in processes including clot formation, tissue granulation and cell recruitment, in a coordinated manner, with direct cross-talk between the osteogenic and immune cells [14].The interplay between immunology systems and bone forming cells is critical for osseointegration and to understand microenvironmental and cellular cues [15]. Specifically the role of macrophages has recently been recognized as critical for bone homeostasis, directly affecting the cross-talk between osteoblasts and osteoclasts [16,17].…”
Section: Introductionmentioning
confidence: 99%